Arsitektur Masjid Sri Alam Dunia di Kecamatan Sipirok, Tapanuli Selatan - Ritonga, Hermansyah; Naldo, Jufri; Ali, M. Nasihudin (Local History & Heritage, 2024)
This study examines the Architecture of Sri Alam Dunia Mosque in the Sipirok District, South Tapanuli. Built in 2010, the mosque has become an icon of religious and cultural significance in the region. The research aims to elucidate the architectural characteristics of the mosque, the factors influencing its design, and its impact on the local community. The research method employed is qualitative descriptive analysis, with data collection through field observation, interviews with community leaders, and documentation studies. The findings reveal that the Architecture of Sri Alam Dunia Mosque reflects a harmony between local tradition and modernity, emphasizing both visual beauty and functionality. The mosque's design also adheres to Islamic principles in layout and ornamentation. Its impact on the local community includes increased pride and cultural identity, as well as a rise in religious tourism visits. In conclusion, the study demonstrates that mosque architecture plays a vital role in strengthening social and religious bonds within communities, while also serving as a symbol of cultural diversity and progress.